Use of Smart Mobile and Web Application Kobotoolbox/ Kobocollect for Community Health Diagnosis: Sharing Experience from the Remote Area of Nepal - Aryal, Umesh Raj; Sanjel, Seshananda; Kafle, Om Prakash; Chhetri, Muni Raj; Shrestha, Yogesh Man; Dhami, Dabal Bahadur (Journal of Karnali Academy of Health Sciences, 2023)
Community Health Diagnosis (CHD) is part of teaching-learning activities at medical and public health schools to recognize the health-related issues in the community, identify social and other problems in depth, and find solutions by shaking hands with community people. Every year, the household survey is conducted by medical, nursing, and public health students as a part of CHD. Our experiences revealed that the student faces several challenges while using paper-based data collection and management during CHD. To overcome such challenges, we used a web-based and smart mobile application called KoboToolbox/KoboCollect to conduct household surveys in CHD in remote areas of Nepal for the first time. Our experience suggests that mobile-based Applications can be used conveniently in CHD which saves time and money for students as well as for schools and can conserve the environment trees. Those students who are not familiar with smart technology need to be trained before using this app.